Socialization of economic and Islamic financial sustainability for student entrepreneurs in Kota Kinabalu, Sabah, Malaysia - Muhammad Haris Riyaldi; Hendra Halim; Ridwan Nurdin; Dg Safrina Ag Budin; Ahmad Nizam; Mohd Rahimie bin Abd Karim; Suddin Lada; Amri (Formosa Publisher, 2024)
The "Socialization of Economic and Islamic Financial Sustainability for Student Entrepreneurs" was a collaborative event between Universitas Syiah Kuala (USK) and Universiti Malaysia Sabah (UMS) on June 25, 2024. It aimed to enhance student entrepreneurs' understanding of Islamic finance and Sharia law. Using the service-learning method, Dr. Dg. Safrina Ag. Budin presented on "Diversification of Islamic Banking Products in Malaysia," and Dr. Ridwan Nurdin discussed "The Uniqueness of Sharia in Aceh." Results showed significant improvement in participants' knowledge and engagement. This activity effectively contributed to promoting sustainable economic and financial practices among student entrepreneurs, aligning with the Sustainable Development Goals.